PENGARUH KOMUNIKASI DAN KERJASAMA TIM TERHADAP KINERJA KARYAWAN PADA CV. MITRA TEKNIK SURABAYA - Raihana Raihana; Mochamad Syaiful Arif (Jurnal Ekonomi, Bisnis dan Social, 2024)
This research aims to find out the description of Communication, Teamwork and Employee Performance at CV. Mitra Teknik Surabaya, to determine the effect of Communication on Employee Performance at CV. Mitra Teknik Surabaya, to determine the effect of teamwork on employee performance at CV. Mitra Teknik Surabaya, to determine the effect of Communication and Teamwork on Employee Performance at CV. Mitra Teknik Surabaya. The sampling technique in this study was Non-Probability Sampling / Saturated Sampling, by distributing questionnaires or lists of statements to 40 respondents (all employees of CV. Mitra Teknik Surabaya) and assisted by SPSS version 25 for the data processing facility. The data analysis method that researchers used in this research is multiple linear regression analysis. After processing the data with SPSS version 25, the authors get the result that in the t statistical test it is found that the Communication variable has a partially significant effect on Employee Performance, and also Teamwork has a partial significant effect on Employee Performance. Whereas in the statistical test f it was found that Communication and Teamwork have a significant effect simultaneously on Employee Performance at CV. Mitra Teknik Surabaya..